К диахронии “цельно-расчлененной” актуализации референта имени через согласующиеся с ним слова в английском языке - Гусейнов, Р. И. (Kalbotyra, 1987)
Here an attempt has been made to substantiate one grammatically specific class of nouns for all the three main periods of English, the constituents of which receive an actualization of number distinctions outside their own boundaries, i. e. in other word-forms either agreed with (finite forms) or correlated to them (pronouns); cf. My family is good. My family are good speakers. When correlated to a prounoun or agreed with a verb in singular they denote undivided wholes, whereas in plural they stand for divided wholes.In Old English they included collective bodies of both persons and things. The number of the latter was very small. In later periods of English they came to denote collective bodies of persons only when used with verbs and pronouns in plural. On the whole their number goes up toward Modern English. Some of them still in Old English developed plural number markers of their own thereby acquiring the capacity to actualize two different meanings of plurality – that of divided wholes (My family are ...) and that of multiplied undivided wholes (families). These two semantic distinctions represent two different degrees of abstraction, the notion of the first being concrete, that of the latter – abstract, resembling, in its turn, the semantics of the plurality of mass nouns (oil – oils: water – waters).